(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
The focus of this paper is on the phenomenological enquiry of the impact of the therapist’s practice of meditation upon his or her therapeutic practice. While there are many findings, this paper focuses on two main findings. The first and most fundamental finding is that meditation is experienced as ’being with what is’. The second and equally important finding is that with the practice of meditation co-researchers experience a transformational change in all aspects of their life including in their interaction with their clients.